Macroeconomic implications of trade diversifiation in Nigeria - Lukman O. Oyelami; Philip O. Alege (CBN Journal of Applied Statistics, 2018)
This study seeks to examine the effects of trade diversification on macroeconomic performance in Nigeria. To achieve this, the study employs bound test of ARDL to determine the existence of cointegration between trade diversification and key macroeconomic variables. We further estimate the short-run and long-run effects of Intensive and Extensive trade diversification on Economic growth and exchange rate movements. The results from bound tests confirm cointegration between trade diversification and economic growth on one hand and trade diversification and exchange rate movements on the other hand. Similarly, the results from our estimations show that trade diversification can propel economic growth in the country. Also, the trade diversification can reduce movements in exchange rate especially extensive diversification thus preventing it from substantial movement that can derail this important variable from its long run equilibrium. The study recommends that policy makers should pursue vigorously both intensive and extensive trade diversification to propel economic growth and guarantee stable exchange rate for the Nigerian currency.
Keywords: F13; F1; C22; E00; 330; ARDL; Diversification; Macroeconomics; Trade